Measuring willingness to pay for Islamic securities to finance prisons: a case study about Isfahan - Iman Bastanifar; Mohammad Reza Heidari; Arman Roshandel (جستارهای اقتصادی, 2019)
Developing capital markets through Islamic securities can improve the efficiency and management of the money market, achieving macroeconomic goals, and financing public sector. One of the most important and costly organizations in the economy is the Prisons' Organization. Despite the numerous needs of the prisons, the financing of Islamic securities is still not applied for this organization. Therefore, it is necessary to measure individuals' willingness to pay for Islamic securities. The present study, seeks to measure the willingness to pay, for both for profit and non-profit Islamic securities to finance prisons and analyze the factors affecting it. The Contingent Valuation Method (CVM) has been used to estimate the willingness to pay and rank-ordered probit model has been used to analyze the effective factors. The findings show that, the average willingness to pay of the citizens of Isfahan for profit Islamic securities is 17000000 Rial per family in one year, and the average of willingness to pay for non-profit securities is 2600000 Rial per family in one year. Also, the variables income, type of assistance, the degree of trust to state institutions and aid intentions at the 95% confidence level have affected purchasing profitable Islamic securities, and age, income, type of assistance, the degree of trust in state institutions and the assurance intention at the 95% confidence level and the prisoners' record at 90% confidence level have affected the probability of purchasing non-profit Islamic securities.